(untitled) (Bulletin KNOB, 2008)
In relation to the architecture of façades, in the 18th century the roof got a less striking, even secondary position in comparison with the high ornamental roof still in vogue in the 17th century. This was expressed in a reduction in height by dividing the span into two or more roof points. In order to give a terraced house more prestige an extra floor was added at the front side of the house with a shallow transverse roof, also called ’liar’. The asymmetrical section of the design of J. Giudici for the town hall in Groningen (1775) may be called a variation on this approach. The need to roof over a large span of a limited height led to the king post roof truss used in the Netherlands in the second half of the 17th century. The principle of a central motice and tenon joint, as used between king post and tie-beam, with wrought iron connections was already known in the late Middle Ages. In those days, however, it still concerned tall, high-pitched roofs which went out of fashion in the 18th century, just as the stacked trestles called ‘broken trusses’ in the 18th century. To what extent did architectonic fashion, commissioner or architect determine the external appearance and thus frequently the internal layout of the roof? This change, or, if you like, various executions in the four stages of one single project assignment, can be strikingly illustrated in the early 18th century on the basis of the design drawings for Le chateau de Lunéville. The French court architect Germain Boffrand (1667-1754) initially made a design with high-pitched roofs, ’projet 1 à hautes toitures’ in which simple rafters with top bracing are to be seen. Within a relatively short period (1708-09) this changed into the seemingly roofless variation ‘projet 3 avec les longes ailes’. Under the low, sometimes flat roofs only king post roof trusses were then to be seen. In greater detail, the 18th century roofs in the Netherlands are characterized by the use of pinewood purlin rafters of which the principal rafters continue from wall plate to ridge. Unlike in the 17th century, (cut) assembly marks were usually omitted. In simple form these roofs may have been constructed with ashlar posts, sometimes unbroken tie-beams, top bracing and spur-ties in which iron connections were increasingly used.